CULTIVATING AWARENESS: EXPLORING THE PERSPECTIVES OF CAMBODIAN VEGETABLE FARMERS ON PESTICIDE USE AND HEALTH RISKS - Chan , Sophea Kimly; Lim, Sokha Vannak (Research Journal of Agriculture (RJA), 2024)
Cambodia, a prominent South East Asian country, has long relied on agricultural production as its primary economic pillar. With 4.5 million hectares of cultivated land, a substantial portion—70 percent—is dedicated to rice, serving as the predominant commodity and income source for the majority of farmers. The remaining 30 percent is allocated to various other food and industrial crops, with an annual increase in cultivation area fueled by the expansion of higher-value crop production and the integration of farmers into markets (ADB, 2021; WB, 2015). In the realm of vegetable production, farmland represents a modest 1.3 percent of the total agricultural land, predominantly owned by smallholders with an average farming area of less than 0.5 hectares. Paradoxically, despite the available arable land, over 50 percent of the country's vegetable consumption relies on imports, particularly from neighboring Vietnam. This import dependency is attributed to factors such as price competitiveness, logistical challenges, and the capacity for year-round production (SNV, 2022; NIS, 2015; FAO, 2014; Schreinemachers et al., 2017). However, concerns arise as pesticide residues in imported vegetables often surpass maximum residue limits, posing a significant risk to consumers (Skretteberg et al., 2015). Compounding this issue, Cambodian vegetable producers are similarly reliant on pesticide use as an indispensable measure for crop protection and a pivotal component in production, crucial for ensuring their income (Schreinemachers et al., 2017; Damalas, 2009). This dual dependence on pesticides in both domestic production and imports raises pressing questions about the overall safety and sustainability of vegetable consumption in Cambodia. This study aims to scrutinize the intricate dynamics of Cambodia's vegetable supply chain, investigating the interplay between domestic production and imports, the prevalence of pesticide residues, and the associated risks to consumer health. By shedding light on these critical aspects, the research seeks to inform policy interventions, promote sustainable agricultural practices, and enhance the safety of the vegetable supply chain in Cambodia